Agricultural export growth and economic development for Tonga : the quest for efficiency : a thesis presented in partial fulfilment of the requirements for the degree of Master of Public Policy at Massey University, Albany, New Zealand - Kautoke-Holani, Alisi Wenonalita (Massey University, 2008)
Neo-liberalism has become the dominant approach to economic development since the 1980s. Based on the economic principle of “efficiency”, the Washington Consensus and its supporters have avidly promoted the neoliberal orthodoxy as the ideal blueprint for the economic development of all countries in every region. However, as this thesis has discovered, the efficiency of public policy is weighed not by its conformity to an ideology but on how effective it responds to the economic and social problems of the population in question. In recent years Tonga has endured severe economic shocks which have pushed its low growth economy to the brink of economic crisis. In response to this crisis, the Government has chosen greater economic liberalisation and private sector – led growth to lead the economy to recovery. The Washington Consensus and its international supporters claim that this is the best policy response for Tonga due to the belief that greater liberalisation leads to greater efficiency. This thesis however believes that at the current dire state of the economy, it is not enough for Tongan public policy to just conform to international views on efficient economic development but to ensure that its economic development policies address the economic and social needs of the general Tongan population. With this in mind, this thesis investigated the role of agriculture in economic development. It identified that for an agriculture-based country such as Tonga, at low levels of growth, agricultural development is fundamental to long term economic growth. This research also revealed that agricultural growth is maximised through trade hence suggesting increased focus on agricultural export development. Based on these findings, this research project set out to verify the efficiency of Government agricultural policies by identifying the views of agricultural exporters and comparing these with Government approaches to agricultural export development in Tonga.
Keywords: Agricultural development; Agricultural export; Economic policy; Tongan public policy; Fields of Research::340000 Economics::340200 Applied Economics::340213 Economic development and growth